An analysis on the efficiency of the Malaysian Islamic banking industry: domestic vs. foreign - Abd Hadi, Fatimah Salwa; Md Saad, Norma (International Association for Islamic Economics, 2010)
This paper examines productivity change of Islamic banks in Malaysiaduring the period 2006 to 2008. The data includes a panel of 12 Islamic banks and the productivity of each bank is analysed using the non-parametric Data Envelopment Analysis (DEA) method or the intermediation approach. In the DEA technique, efficiency is measured by the Malmquist index. We model Islamic banks in Malaysia as multi-product firms producing two outputs (total loan and income) by employing three inputs (total deposit, labour, fixed asset). Overall results suggest that scale efficiency dominates the pure technical efficiency effects in determining Malaysian Islamic banks’ overall or technical efficiency. Another important finding derived from the study is that Malaysian-owned Islamic banks’ performance is better compared to their foreign-owned counterparts. The findings of the study are important for Islamic banks in Malaysia to improve or maintain the ability to become more competitive and provide a viable and better alternative to the conventional banking system.